SEBARAN GUA DAN CERUK PRASEJARAH DI DESA PADALERE UTAMA - Hendra Saputra; Syahrun Syahrun; Salniwati Salniwati (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
The issues addressed in this research are: (1) What prehistoric caves and rock shelters are present in Padalere Utama Village, Wiwirano District, North Konawe Regency? (2) What are the characteristics of the prehistoric caves and rock shelters in Padalere Utama Village, Wiwirano District, North Konawe Regency? This study employs inductive reasoning, where specific observations are generalized into broader conclusions. Data collection techniques used in this research include library research, field data (observation), and interviews. Additionally, data analysis techniques applied are morphological analysis and contextual analysis. Based on the research findings, there are approximately 14 caves and 2 rock shelters in Padalere Utama Village, each with the potential for containing archaeological remains. Some of the archaeological remains that can be found include mollusks, bones, pottery, stone tools, ceramics, and rock art. Among the various caves and rock shelters discovered, mollusk remains dominate. Furthermore, the characteristics of the caves and rock shelters can be observed through their morphological conditions, environmental settings, and the state of the archaeological remains. The distribution of prehistoric caves and rock shelters in Padalere Utama Village, supported by an environment conducive to the life of prehistoric humans, indicates the presence of culture, civilization, and human migration during that period.